Criminal procedural neoinquisitorialism and the judger's contamination with the acts of investigation: the internal burla in brazilian criminal proceedings as obstacles to the contradictory - Melo, Marcos Eugênio Vieira (2020)
This article analyzes the permanence of the Inquisitory culture in Latin America and the weight of the Inquisitory mentality within the Brazilian criminal process, especially in the preliminary phase, which deals with the main nucleus of the probative formation used by the judge in the sentence, in order to answer the following problem: what are the main obstacles in the Brazilian criminal process today so that there is an effectively contradictory judgment? For this purpose, it is evaluated through the study of classical and contemporary criminal process doctrines the implications on the legitimacy admitted by the Brazilian criminal process, mainly through the “dirty game” brought by the breach of article 155 of the Code of Criminal Procedure, which contaminates the magistrate with the police inquiry and in conjunction with signifiers such as “free conviction” and “real truth” serve as obstacles to judgment based solely on contradictory acts and the participation of all parties involved in the process.